The dual role of a loop with low loop contact distance in folding and domain swapping - Linhananta, Apichart (Cold Spring Harbor Laboratory Press, 2002)
α helices, β strands, and loops are the basic building blocks of protein structure. The folding kinetics of α helices and β strands have been investigated extensively. However, little is known about the formation of loops. Experimental studies show that for some proteins, the formation of a single loop is the rate-determining step for folding, whereas for others, a loop (or turn) can misfold to serve as the hinge loop region for domain-swapped species. Computer simulations of an all-atom model of fragment B of Staphylococcal protein A found that the formation of a single loop initiates the dominant folding pathway. On the other hand, the stability analysis of intermediates suggests that the same loop is a likely candidate to serve as a hinge loop for domain swapping. To interpret the simulation result, we developed a simple structural parameter: the loop contact distance (LCD), or the sequence distance of contacting residues between a loop and the rest of the protein. The parameter is applied to a number of other proteins, including SH3 domains and prion protein. The results suggest that a locally interacting loop (low LCD) can either promote folding or serve as the hinge region for domain swapping. Thus, there is an intimate connection between folding and domain swapping, a possible cause of misfolding and aggregation.